Individual Dismissal Regulation in Spain after the 2012 Reform (Real Decreto- Ley 3/2012, Ley 3/2012 y Real Decreto-Ley 20/2012) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
The recent regulatory amendments carried out in Spain have significantly affected the individual dismissal regulation. The article highlights how legitimize grounds for dismissal have been modified, especially those regarding economic reasons and absence from work. The farreaching changes in the juridical consequences of unfair dismissal are analyzed in the second part of the article. Topics discussed include reduction of the redundancy pay and its new calculation procedure, and constrainsto the right to receive procedural salary, and how it has caused the disappearance of the so-called “express dismissal”. In the last part of the article, the author reviews the exclusion of compulsory retirement clauses from collective agreements and the changes in direct responsibility of the Wage Guarantee Fund (FOGASA) in the caseof enterprises with less than 25 employees implementing collective justified redundancieson economic grounds.
Keywords: Individual dismissal; 2012 Reform; Law 3/2012; Royal Decree-law 3/2012; Royal Decree-law 20/2012; Grounds for dismissal; Economic reasons; Absence from work; Unfair dismissal; Procedural salary; Express dismissal; Compulsory retirement clauses; Direct res